2022
DOI: 10.13075/ijomeh.1896.01816
|View full text |Cite
|
Sign up to set email alerts
|

Hearing status of people occupationally exposed to ultrasonic noise

Abstract: The aim of the study was to evaluate the hearing status of operators of low-frequency ultrasonic devices compared to employees exposed to audible noise at a similar A-weighted sound pressure level (SPL) but without ultrasonic components. Material and Methods: Standard pure-tone audiometry, extended high-frequency audiometry (EHFA), transient-evoked otoacoustic emissions (TEOAE), and distortion-product otoacoustic emissions (DPOAE), as well as questionnaire surveys were conducted among 148 subjects, aged 43.1±1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…This may explain differences between our findings and those of other studies, which have looked at the effect of SOAEs on HTs and DPOAEs. Despite this note of uncertainty, our study confirms the results of earlier works that have shown that HTs and DPOAEs in the EHF band seem to show promise for identifying early signs of hearing loss [17,48,49].…”
Section: Discussionsupporting
confidence: 89%
“…This may explain differences between our findings and those of other studies, which have looked at the effect of SOAEs on HTs and DPOAEs. Despite this note of uncertainty, our study confirms the results of earlier works that have shown that HTs and DPOAEs in the EHF band seem to show promise for identifying early signs of hearing loss [17,48,49].…”
Section: Discussionsupporting
confidence: 89%
“…In all these studies on industrial workers, significant co-exposure to high frequency sound in the audio range was present. In order to mitigate the potential bias related to noise co-exposure, Dudarewicz et al (2022) used a control group that was matched to daily noise exposure level (A-weighted SPL equivalent to continuous 8-h shifts), age, sex, as well as tenure (as proxy for industrial noise exposure duration). In their cross-sectional study HTL as well as transient-evoked otoacoustic emissions (TEOAE) and distortion-product otoacoustic emissions (DPOAE) of workers with and without ultrasound exposure during work shifts (but with similar A-weighted audible noise co-exposure SPL) were compared.…”
Section: Biological Endpointsmentioning
confidence: 99%